Prognostic impact of secondary prevention after coronary artery bypass grafting—insights from the TiCAB trial. (9th February 2022) - Heer, Tobias; von Scheidt, Moritz; Boening, Andreas; Heyken, Clarissa; Gusmini, Friederike; de Waha, Antoinette; Kuna, Constantin; Fach, Andreas; Grothusen, Christina; Oberhoffer, Martin; Knosalla, Christoph; Walther, Thomas; et al.
Abstract: OBJECTIVES: There are disparities in the adherence to guideline-recommended therapies after coronary artery bypass graft (CABG). We therefore sought to evaluate the effect of guideline-adherent medical secondary prevention on 1-year outcome after CABG. METHODS: Data were taken from the randomized 'Ticagrelor in CABG' trial. From April 2013 until April 2017, patients who underwent CABG were included. For the present analysis, we compared patients who were treated with optimal medical secondary prevention with those where 1 or more of the recommended medications were missing. RESULTS: Follow-up data at 12 months were available in 1807 patients. About half (54%) of them were treated with optimal secondary prevention. All-cause mortality [0.5% vs 3.5%, hazard ratio (HR) 0.14 (0.05–0.37), P < 0.01], cardiovascular mortality [0.1% vs 1.7%, HR 0.06 (0.01–0.46), P = 0.007] and major adverse events [6.5% vs 11.5%, HR 0.54 (0.39–0.74), P < 0.01] were significantly lower in the group with optimal secondary prevention. The multivariable model for the primary end point based on binary concordance to guideline recommended therapy identified 3 independent factors: adherence to guideline recommended therapy [HR 0.55 (0.39–0.78), P < 0.001]; normal renal function [HR 0.99 (0.98–0.99), P = 0.040]; and off-pump surgery [HR 2.06 (1.02–4.18), P = 0.045]. CONCLUSIONS: Only every second patient receives optimal secondary prevention after CABG. Guideline adherent secondary prevention therapy is associated with lower mid-term mortality and less adverse cardiovascular events after 12 months. Abstract : Patients after coronary artery bypass graft (CABG) for severe coronary artery disease continue to be at higher risk for ischaemic events due to progression of the disease in their native vessels or due to degeneration of the grafts.